O mito judaico-cristão da criação: uma leitura retórico-passional - Domingues, Luan Marques (2020)
The perspective in which the rhetoric fits is that of the speeches that aim to win the adhesion and trigger an action, on the part of the audience. It is in this way that we enter into Aristotle's thought when conceiving rhetoric as an area that turns to the investigation of what is suitable for persuasion. Thus, it is an art! The art of speaking well. In this perspective, all persuasive action takes place by means of a rhetorical tripod: a speaker (holder of an ethos) who enunciates his speech (elaborated through logos) aiming to attract his audience (pathos' receptacle) through the aroused passions. In this way, the audience is passionately encouraged and rationally driven to adhere to a thesis proposed by the speaker about a certain theme or issue. Immersed in this theoretical universe, we decided to study the mythological text of creation (derived from the Judeo-Christian belief) from the Aristotelian passions' perspective. The chosen text strongly influences the way in which people deal with issues related to the origin, structure and organization of the cosmos, as well as interpreting the genesis and purpose of humanity. The objective of this research is, therefore, to outline a reading of the Judeo-Christian text of creation, contained in the Bible in its first book called Genesis, in chapters I and II, through the bias of the rhetoric of the passions proposed by Aristotle. We intend, with this study, to verify the possible passions aroused in the audience of that time, around 400 BC. We still bring up the reflection of the possibility of rhetorical-passionate reading being an effective tool for reading diverse texts, especially when their contexts of production and reception are not easily recoverable. We believe that this type of reading can provide the reader with greater freedom, since it frees him from keeping the text literal and leads him to a new incursion provided by the richness of the polysemic perspectives of an utterance. In order to respond to the theoretical-methodological purposes outlined in this work, we carried out a bibliographic-descriptive research based on the pillars of rhetorical art, with emphasis on the pathos' argumentative instance regarding specifically to the emotions described by Aristotle (2012) and taken up by Figueiredo (2018, 2019) when she proposes her “Pathways of passion”. For a greater detailing of the text chosen by us for analysis, it is also necessary to reflect on the discursive genre that encompasses it. After plausible inferences, we proceeded to a qualitative analysis of the corpus in order to verify the applicability of our conjectures. KEYWORDS: Creation myth; Rhetoric; Aristotle; Passions; Literality of the text.